Measuring Latency Variation in the Internet - Høiland-Jørgensen, Toke; Ahlgren, Bengt; Hurtig, Per; Brunstrom, Anna (Karlstad University, 2018)
This is the companion web site and dataset to the paper "Measuring Latency Variation in the Internet" which was published at ACM CoNEXT '16.

Also published at https://www.cs.kau.se/tohojo/measuring-latency-variation/
Keywords: Computer Sciences; Datavetenskap (datalogi)